ANALYSIS OF THE RESULTS OF TREATMENT OF 93 PATIENTS WITH POST-COVID THROMBOSES OF THE CAVERNOUS SINUS IN THE CONDITIONS OF THE DEPARTMENT OF PURULENT SURGERY - Ulugbek K. Kasimov; Ulugbek P. Abdullaev; Kakhramon X. Boboev; Diyora U. Sultanova (Central Asian Journal of Medicine, 2022)
Speaking of post-covid complications, the development of cavernous sinus thrombosis, which is a single cerebral vein and sinus thrombosis, with the development of a characteristic clinical syndrome, is alarming. There is an increase in the growth of this type of complication. In patients with COVID-19, the starting point is the presence and progression of fungal microflora, which manifests itself as rhino-orbital mucormycosis - ROM. Specialists faced the problem of managing these patients, which consists in late diagnosis and a corresponding high mortality rate. A number of unresolved issues have been identified, these are the causes and timing of the development of cavernous sinus thrombosis, criteria for the risk of development, determination of conservative and surgical tactics.